Physiological and pathophysiological effects of L-tryptophan’s metabolites on the brain and immunity – a challenge for drug development - Petar Iliev; Simeon Ivanov; Simeon Lazarov; Georgeta Bocheva (Pharmacia)
The dysregulation of the kynurenine branch from tryptophan (TRP) metabolism can cause an imbalance between neuroprotective kynurenic acid and neurotoxic kynurenine metabolites in some psychiatric and neurodegenerative disorders. Therefore, the modulation of TRP metabolism may contribute to novel therapeutic strategies for several neuropsychiatric diseases. Targeting L-TRP-kynurenine pathway enzymes, particularly involving indoleamine 2,3-dioxygenase-1, tryptophan 2,3-dioxygenase, kynurenine 3-monooxygenase, and kynurenine aminotransferase II, is a promising approach. The future development of potent selective inhibitors of these enzymes with a good safety profile would be a potential new avenue for the treatment of many diseases. The essential amino acid L-Tryptophan, together with its metabolites, plays a key role in diverse physiological and pathophysiological processes in the brain, especially in neurodegenerative and psychiatric disorders and autoimmunity. Also, TRP is a vital biochemical precursor for several functional neuroactive molecules, including serotonin and melatonin, which are of great importance for memory and learning, emotional regulation, circadian cycle, hunger, pain, etc. This article aims to underscore the links between tryptophan’s metabolism and certain diseases of the central nervous system.